GAMBARAN RESILIENSI PADA MANTAN PASIEN COVID-19 - Tria Pratiwi (Jurnal Inovasi Penelitian, 2021)
Resilience is a person's psychological resilience when faced with problems or difficulties. This study aims to determine the description of the resilience of former Covid-19 patients. This study uses a qualitative method with a phenomenological study approach. The subjects in the study were two former Covid-19 patients from the city of Padang who had undergone a post-quarantine period. Collecting data using semi-structured interviews. The findings from the results of this study are that the two subjects after undergoing post-quarantine period of more than two months, but they still experience PTSD, anxiety and fear